Regional disparities in apprentice attrition rates: heat and quarter four's significance in northern Australia. (4th May 2017) - Zoellner, Don; Brearley, Matt; Oppermann, Elspeth
Abstract: Apprenticeship completion rates have remained persistently low for decades in spite of broad agreement over the causes of non-completions. A possible factor missing from these explanations is climate, particularly in northern Australia where traditional trade apprentices are exposed to extreme conditions and exert themselves. We hypothesize that: the onset of hotter, more humid weather in northern Australia during the fourth quarter of the calendar year would be reflected by an increase in trades' apprenticeship withdrawals and cancellations. Using the entire National Apprentice and Trainee Collection, completion and attrition data were geographically categorized into north and south Australia. Statistical analyses identified a clear difference in trade occupation's cancellations and withdrawals. Regionally specific climate variables are briefly examined, further supporting the claim that heat stress appears a likely contributor. These cross-disciplinary findings have a broader significance as apprenticeship completions contribute to socio-economic growth and the public policy agenda of northern development.